Carvacrol Enhance Apoptotic Effect of 5-FU on MCF-7 Cell Line via inhibiting P-glycoprotein: An In-silco and In-vitro Study - Ghorbanzadeh, Vajihe; Aljaf, Karwan Anwar Hassan; Wasman, Hunar Mustafa; Pirzeh, Lale; Azimi, Saleh; Dariushnejad, Hassan (Drug Research, 2022)
Background P-glycoprotein (P-gp), is an ATP-dependent efflux transporter and overexpressed in cancer cells which is responsible for drug resistance and transportation of anticancer agents out of cells. Hence, P-gp inhibition is a promising way to reverse multi-drug resistance, finding a suitable inhibitor is essential. Carvacrol, an active compound of thyme, has been shown anticancer properties in several types of cancers but the mechanisms underlying this effect remain unclear. Here, we evaluated the inhibitory effects of carvacrol on P-gp by In-silco and in-vitro studies.Method carvacrol was docked against P-gp via autodock vina software to identify the potential binding of this agent. Verapamil, a well-known P-gp inhibitor, was selected as the control ligands. Cell proliferation and apoptosis were assessed using MTT assay and ELISA cell death assay, respectively.Results It was observed that carvacrol exhibited appropriate affinity (−7 kcal/mol) to drug binding pocket of P-gp when compared with verapamil that showed binding affinities of −8 kcal/mol. The result of MTT assay showed a dose-dependent inhibitory effect of carvacrol and 5-FU. Data of apoptosis assay showed that combining carvacrol with 5-FU increased apoptotic effect of 5-FU 6.7-Fold rather than the control group. This ability to enhance apoptosis is more than the combination of verapamil and 5-FU (4.26-Fold).Conclusion These results provide important evidence that carvacrol may be a promising agent able to overcome P-gp-mediated MDR.
Keywords: Breast cancer; Carvacrol; Molecular docking; Multi Dug Resistance; P-glycoprotein